Calculation of the electron spin relaxation time in a quantum limit using a state-independent projection reduction method. (27th December 2017) - Kang, Nam Lyong
Abstract: A new formula for determining the electron spin relaxation time in a system of electrons interacting with acoustic deformation phonons through phonon-modulated spin–orbit coupling is derived using the state-independent projection reduction method. The spin flip and conserving processes are explained in an organized manner because the obtained results properly contain the distribution functions for electrons and phonons. The electron spin relaxation time is calculated directly from the lineshape function without calculating the magnetic susceptibility. The temperature ( T ) and magnetic field ( B ) dependences of the electron spin relaxation time ( T 1 ) in Si are shown by T 1 ≈ T −1.55 and T 1 ≈ B −1.96 in the quantum limit, respectively.